2009
DOI: 10.1186/1471-2407-9-76
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of risk factors, beliefs and practices of female healthcare professionals towards breast cancer in a tertiary institution in Lagos, Nigeria

Abstract: BackgroundBreast cancer is the leading female malignancy in Nigeria. Screening for early detection has led to reduction in mortality from the disease. It is known that attitudes of physicians and motivation by community nurses influence uptake of screening methods by women. This study aims to investigate knowledge of breast cancer risk factors, beliefs about treatment and practice of screening methods among a cohort of female healthcare professionals in Lagos, Nigeria.MethodsA cross-sectional study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
62
7
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 32 publications
15
62
7
2
Order By: Relevance
“…Breast self-examination was practiced regularly by the 91.9% undergraduate students of Klang valley, Malaysia 13 . However, in present study, only 9 (7.2%) women had ever tried BSE though none of them did it on More than 65% Gurdaspur women believed that breast cancer can be cured whereas 86% Nigerian females 22 were optimistic that breast cancer can be treated if detected in early stage by screening methods like BSE, CBE, mammography etc. A study conducted by Dey et al, 23 reported that majority (73.8%) of Delhi women believed that surgical removal of lump in the breast is the best treatment for breast cancer.…”
Section: Discussionmentioning
confidence: 81%
“…Breast self-examination was practiced regularly by the 91.9% undergraduate students of Klang valley, Malaysia 13 . However, in present study, only 9 (7.2%) women had ever tried BSE though none of them did it on More than 65% Gurdaspur women believed that breast cancer can be cured whereas 86% Nigerian females 22 were optimistic that breast cancer can be treated if detected in early stage by screening methods like BSE, CBE, mammography etc. A study conducted by Dey et al, 23 reported that majority (73.8%) of Delhi women believed that surgical removal of lump in the breast is the best treatment for breast cancer.…”
Section: Discussionmentioning
confidence: 81%
“…Another study in Nigeria in 2009 reported that 86.7% had the same believe [28]. The most common risk factors for BC identified by participants were; family history of BC (91.9%), old age (82.1%), increase breast density (78%), late age at menopause (75.6%) and radiation exposure (64.2%).…”
Section: Discussionmentioning
confidence: 99%
“…In current study 95.9 % of participants believed that early detection and treatment of breast cancer affects survival. Also, all participants (100%) in Ghanem, et al, study believed that BC is curable if detected early [27] and 91.1% in Ibrahim et al, [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 43-item survey was adapted from existing surveys designed to test knowledge about breast cancer epidemiology, risk factors, and screening in general populations in the United States and certain low-and middle-income countries [24][25][26][27][28][29]. The instrument was designed in collaboration with Mexican institutions and investigators who had conducted previous breast cancer research in Mexico.…”
Section: Survey Instrumentmentioning
confidence: 99%